Memahami Teori dan Model Kompetensi Lintas Budaya: Studi Tinjauan Literatur - Musfira, Nurul; Ahmadin, Ahmadin; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
Intercultural communication is the process of conveying messages between individuals or groups with different cultural backgrounds, involving not only linguistic aspects but also values, norms, and attitudes that constitute cultural identity. This study aims to explain the theories and models of intercultural communication through a literature review, including Milton Bennett's Developmental Model of Intercultural Sensitivity (DMIS), Deardorff's model of intercultural competence, and the concept of cultural intelligence introduced by Earley and Ang in 2003. The results of the study show that DMIS helps to understand how individuals respond to cultural differences, while the intercultural competence model emphasises the ability to establish positive relationships in a pluralistic society. Meanwhile, the concept of cultural intelligence explains how individuals can develop adaptive skills in dealing with cultural diversity. Overall, intercultural competence encompasses aspects of attitude, knowledge, skills, and awareness that form the foundation for harmonious interactions between individuals in a diverse cultural context.